Maoism, Political Violence and Terrorism in Italy - Gabbas, Marco (Terrorism and political violence, 2022)
When assessing political violence and terrorism in recent Western European history, the case of Italy stands out. The 1970s—the anni di piombo or “lead years”—saw an incredible level of political violence, leading certain observers to openly speak about terrorist violence. However, violence continued to a lesser extent even in the 1980s. This article deals with leftist political violence in that period and argues that Maoism was one of its triggers/inspirations. The Italian case stands out also because these high levels of leftist political violence were not linked to nationalist grievances, as was the case in Ireland (IRA) or the Basque Country (ETA). Maoism pushed many on the Italian revolutionary Left to take up arms against the bourgeois state. They did not take Mao’s proclamations of violence and revolution (“power comes from the barrel of the gun”) abstractly. As China opposed Soviet peaceful coexistence on an international level, the Italian revolutionary Left opposed it on a national ground. The pervasiveness of this Maoist call to arms in Italy can be seen looking at the example of the “new” Red Brigades at the turn of the twenty-first century.